Analysis of 48-Hour Blood Pressure Monitoring in Clinical Indicators and Ambulatory Observations as a Topic of Special Attention to Improve the Effectiveness of Arterial Hypertension Treatment in Patients with Diabetes - o’g’li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2023)
Effective blood pressure (BP) control is critical to reducing the risk of cardiovascular complications in patients with arterial hypertension (AH) and type 2 diabetes mellitus (DM). As a rule, routine monitoring is limited to measuring blood pressure at a doctor's appointment (office measurement), which does not always reflect the true state of hemodynamics. Purpose of the study– to analyze the indicators of office and ambulatory 48-hour blood pressure monitoring (ABPM) in hypertensive patients without diabetes and with type 2 diabetes. Material and methods. The study included 83 outpatients with hypertension who received antihypertensive therapy, of which 36 (43.4%) had concomitant type 2 diabetes. All of them underwent a clinical examination with assessment of office blood pressure indicators, as well as laboratory examination (clinical and biochemical analysis of blood, urine) and instrumental examination (ABPM, echocardiography). Results. According to office monitoring data, achievement of target blood pressure values was noted in 31.9% of patients without diabetes and 8.4% of people with type 2 diabetes. According to ABPM results, ineffective hypertension control was registered in 70.2 and 80.6% of patients, respectively. Patients with diabetes were more likely to have uncontrolled hypertension with a significant increase in systolic blood pressure (SBP) and pulse blood pressure (PBP) at night. The degree of nocturnal decrease in SBP significantly correlated with the duration of type 2 diabetes, and the average daily PBP correlated with the level of fasting blood glucose and glycated hemoglobin. Conclusion. Despite comparable adherence to antihypertensive therapy in both groups, patients with type 2 diabetes were less likely to achieve target blood pressure values both during office measurements and ABPM. Almost every seventh person with type 2 diabetes had a disturbance in the daily blood pressure profile according to the Knight-Picker type, which requires special attention when managing this category of patients.